PENGARUH LINGKUNGAN KERJA TERHADAP KUALITAS PELAYANAN (Studi Kasus Di Puskesmas Kecamatan Tahuna Barat Kabupaten Kepulauan Sangihe) - DAHAR, VIVIYANTI; PANGKEY, MASJE; LALOMA, ALDEN (Sam Ratulangi University, 2019)
This study moved on to the phenomenon of the location of the study regarding the existence of some of thecommunity users of health services in the Tahuna Barat Puskesmas about the inadequate quality ofhealth services provided by puskesmas officers. Thus, this study aims to determine the extent of theinfluence of the work environment on service quality in the Tahuna Barat District Health Center, SangiheIslands District. Using descriptive methods and quantitative approaches, the data collected through thedistribution of Research Questionnaires (questionnaires) was analyzed using Frequency Table analysistechniques, while testing research hypotheses used statistical inferencing techniques, such as productmoment correlation analysis techniques and simple linear regression.The results of data analysis showthat (1) both the working environment (X) and the health service quality variable in the Tahuna BaratPuskesma are in the moderate to high category. (2) The results of correlation analysis and simple linearregression show that the work environment has a positive and significant effect on the quality of healthservices with a degree of determination of 38.9%. Thus, the results of this study empirically justify theunderlying theories so that the hypothesis The work environment has a significant influence on thequality of services in the Tahuna Barat District Health Center, Sangihe Islands District, it can be acceptedempirically very convincingly.Referring to the results of this study, it can be suggested: To improve thequality of service even higher, the management of the Tahuna Barat District Health Center, especially thelocal government of Sangihe Islands District, needs to conduct technical training for Puskesmas staff andnurses to improve their performance in providing health services people in needKeyword work : Enviroment, Service Quality, Health Center